Multilateration in Learning Indonesian Language for Foreign Speakers (BIPA) Based on Local Color Literature Betawi at Uin Syarif Hidayatullah Jakarta - Ahmad Bahtiar; Agung Nasrullah (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2019)
Language related to culture. Like other languages, Indonesian is also heavily influenced by local cultures. For this reason, as an Indonesian Language teaching strategy for Foreign Speakers (BIPA) must also introduce cultures in Indonesia. The model used for the learning is local Betawi color-based multiliteration. With multiliteration learning not only teaches linguistic aspects but also culture includes local identity, beliefs, professions, habits, and so on. The choice is based on the location of  the study, namely Syarif Hidayatullah State Islamic University located in Jakarta, which is dominated by the Betawi community. In addition, Betawi is a representation of the Indonesian people actually. Local color literature used for this model is prose in the form of a collection of Terang Bulang short stories, Terang in Kali and Cerita Keliling Jakarta by S.M. Ardan and old poems in the form of pantun. With multiliteration, it is expected that BIPA learners in addition to having linguistic abilities can also understand Indonesian culture, especially Betawi. Thus, BIPA learners have an impression that they are motivated to learn Indonesian and use it on various occasions.